2003
DOI: 10.1182/blood-2002-12-3733
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism in heme oxygenase-1 gene promoter is associated with susceptibility to oxidant-induced apoptosis in lymphoblastoid cell lines

Abstract: Heme oxygenase-1 (HO-1) confers cytoprotection against oxidative stress. A (GT)n dinucleotide repeat in the 5-flanking region of human HO-1 gene shows length polymorphism, which was classified into S (< 27 GT), M (27-32 GT), and L alleles (> 33 GT). Polymorphism in the HO-1 gene promoter was shown to be associated with susceptibility to pulmonary emphysema and restenosis after angioplasty. However, the biologic mechanism underlying these associations is still unclear. To examine this issue, we established lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 17 publications
9
142
3
Order By: Relevance
“…In the present study, we tested the hypothesis that individual capacity to upregulate HO-1 is genetically determined and that reduced HO-1 expression may contribute to the development of coronary atherosclerosis. Consistent with the notion that transcriptional activity of the HO-1 gene decreases with increasing numbers of (GT)n repeats (36), patients with the L/ L genotype in the present study showed a lower level of ΔHO-1 mRNA than patients carrying other genotypes, indicating that the capacity for HO-1 upregulation is, at least in part, genetically regulated. Consistent with this notion, the ΔHO-1 mRNA results were reproducible (the CV was 7.2%).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we tested the hypothesis that individual capacity to upregulate HO-1 is genetically determined and that reduced HO-1 expression may contribute to the development of coronary atherosclerosis. Consistent with the notion that transcriptional activity of the HO-1 gene decreases with increasing numbers of (GT)n repeats (36), patients with the L/ L genotype in the present study showed a lower level of ΔHO-1 mRNA than patients carrying other genotypes, indicating that the capacity for HO-1 upregulation is, at least in part, genetically regulated. Consistent with this notion, the ΔHO-1 mRNA results were reproducible (the CV was 7.2%).…”
Section: Discussionsupporting
confidence: 77%
“…Both can alter the basal level of HO-1 expression as well as in response to stressors (32). Individuals with short (GT)n repeat lengths are "high" HO-1 expressors compared to those individuals with long (GT)n) repeats (33). Several studies indicate that the ability to upregulate HO-1 expression is an important protective factor in some diseases (e.g., cardiovascular disease and renal transplantation) (32).…”
Section: Correlation Of Treg/teff Ratios and Nec Scoresmentioning
confidence: 99%
“…DNA polymorphisms which impair or reduce HO-1 response may therefore lead to increased risk of endothelial dysfunction and vascular disease, including resolution of venous thrombosis [14]. Human patients with shorter HMOX1 promoter (GT) n repeat alleles might benefit by having a stronger inducible heme oxygenase response [15,26], and indeed, long alleles were associated with increased risk of recurrent VTE in the only other study to date to examine the role of this polymorphism in VTE [16].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from recent studies indicate that 50-73% of patients with VTE presented in an outpatient setting [28,29]; therefore our findings are only representative of individuals with VTE severe enough to require hospitalization. Finally, although longer HMOX1 (GT) n promoter repeats have been associated with impaired inducible heme oxygenase [15,27,30], no functional measurements of expression levels or enzyme activity were available in our patient samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation